2010
DOI: 10.1007/s10336-010-0517-9
|View full text |Cite
|
Sign up to set email alerts
|

Female-biased incubation and strong diel sex-roles in the Two-banded Plover Charadrius falklandicus

Abstract: The relative contributions of males and females to incubation, and the diel schedules by which incubation is shared, are important breeding system traits. We used infra-red sensitive cameras to record incubation patterns at 13 nests of the Two-banded Plover Charadrius falklandicus in the Falkland Islands during both day and night. Because predation risk can affect incubation behaviour, we also recorded the diel pattern of nest predation in the wider study population. We found high nest attendance, femalebiased… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 28 publications
0
11
0
Order By: Relevance
“…predators can detect incubators before incubators can detect predators, either because of structural complexity of habitats or because of the relative visual abilities of incubators and predators). We argue that high depredation risk by visual predators may answer the question of why in many other Charadrius species the bright males are more likely to incubate at night [31][32][33]. Such an adaptation requires clear day/night differences, which are available in lower latitudes during the breeding season but not at high arctic latitudes with permanent daylight during the breeding season [50][51][52].…”
Section: Discussionmentioning
confidence: 90%
“…predators can detect incubators before incubators can detect predators, either because of structural complexity of habitats or because of the relative visual abilities of incubators and predators). We argue that high depredation risk by visual predators may answer the question of why in many other Charadrius species the bright males are more likely to incubate at night [31][32][33]. Such an adaptation requires clear day/night differences, which are available in lower latitudes during the breeding season but not at high arctic latitudes with permanent daylight during the breeding season [50][51][52].…”
Section: Discussionmentioning
confidence: 90%
“…If anything, males are the more ornamented sex 74,75 and hence should incubate during the night, which is not the case. Importantly, the sexual colour dimorphism of Northern Lapwings is similar to sexual colour dimorphism of other Charadrius species with predominantly male night incubation 11,7678 . Alternatively, Northern Lapwing (and Pluvialis ) males might be less efficient incubators, e.g.…”
Section: Discussionmentioning
confidence: 57%
“…For instance, Two‐banded Plovers Charadrius falklandicus show a similar incubation pattern but females may be at greater risk, as all nest predations were filmed during daylight (St Clair et al . ). Despite several comprehensive studies of shorebird species, few have observed sex‐related adult survival (Larson et al .…”
Section: Discussionmentioning
confidence: 97%
“…The survival of male St Helena Plovers could be compromised if they incubate largely at night, like males of several other Charadrius species (Kosztol anyi & Sz ekely 2002, St Clair et al 2010, as this is the active period of most predators of breeding plovers on St Helena. Amat and Masero (2004) found male Kentish Plovers Charadrius alexandrinus, which show similar partitioning of incubation, were more likely to be predated at the nest than females.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation